2020
DOI: 10.1016/j.radcr.2020.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Use of drug-coated balloons in the management of a recalcitrant postsurgical hepatic vein stenosis in a pediatric patient

Abstract: Drug-coated balloons (DCB) are a treatment alternative to conventional angioplasty in arterial, hemodialysis fistulas, and venous stenoses. This case report describes a child with the diagnosis of hepatoblastoma treated with chemotherapy and a right extended hepatectomy with venous reconstruction. The patient presented with signs and symptoms of portal hypertension due to a hepatic venous outflow obstruction secondary to stenosis of the surgical anastomosis. The response to conventional angioplasty was limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In 2022, Zheng et al reported another case about an 18-year-old girl who had severe stenosis in the proximal RCA sequelae with KD was treated with DCB and had an excellent result at one-year follow-up (10). Previously, limited case reports about paclitaxel-coated balloon treatment for renal artery, hepatic vein, and pulmonary artery stenosis in children had been published (11)(12)(13). To date, no severe adverse effects of the paclitaxel-coated balloon have been found in children.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Zheng et al reported another case about an 18-year-old girl who had severe stenosis in the proximal RCA sequelae with KD was treated with DCB and had an excellent result at one-year follow-up (10). Previously, limited case reports about paclitaxel-coated balloon treatment for renal artery, hepatic vein, and pulmonary artery stenosis in children had been published (11)(12)(13). To date, no severe adverse effects of the paclitaxel-coated balloon have been found in children.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 The use of drug-coated balloons of PV stenosis in children has also been described. 13 Hepatic Vein and Inferior Vena Cava Obstruction Hepatic vein and inferior vena cava (IVC) complications are less frequent than other vascular complications, occurring in less than 1.5% of cases, and are more common in the pediatric population and after a redo transplant. They can be acute or chronic and lead to thrombosis or stenosis, frequently occurring at the site of the surgical anastomosis.…”
Section: Portal Vein Obstructionmentioning
confidence: 99%
“…The use of drug-coated balloons has been described for the treatment of portal vein stenosis in children. 13 Stents might be needed in case of a poor result after PTA or complication (e.g., dissection, rupture). Small patients have a higher incidence of spasm in response to mechanical stimulus and having nitroglycerin or other vasodilators available is recommended.…”
Section: Liver Transplant Interventionsmentioning
confidence: 99%